Justification of the possibility of using psychopharmacotherapy to overcome the negative impact of the Russian war on the population’s mental health - Orlov Oleh Viktorovych (Insight: the psychological dimensions of society, 2022)
The research purpose is to characterize Psychedelic- Assisted Therapy (PAT) and outline prospects for its implementation in Ukraine. Methodology and methods. Methods of theoretical analysis of scientific literature were used. Results. It was found that according to preliminary estimates, at least 23.5 million Ukrainian citizens are at risk of mental health deterioration: up to 20.0% – moderate and severe; about 70.0% – mild. It is indicated that one of the ways to overcome that kind of problem is to introduce psychotherapy augmented by certain psychoactive substances (MDMA, psilocybin, ketamine, etc.) in Ukraine. It is noted that the combined method has been designated as a breakthrough therapy in the USA since it is three times more effective than traditional psychotherapy methods and twice more effective than traditional drug treatment for PTSD (post-traumatic stress disorder) with shorter treatment duration and similar safety. It is emphasized that in the pre-war period, Ukraine, with the support of international partners, began work on creating a theoretical scientific basis and human resource development for further PAT implementation. It is noted that PAT implementation is now impossible in Ukraine due to the operation of outdated legislation that does not take into account the latest scientific achievement. In particular, it refers to the Resolution of the Cabinet of Ministers of Ukraine dated May 6, 2000, No. 770, which prohibits the use of psychotropic substances necessary for PAT, and the Order of the Ministry of Health of Ukraine dated April 15, 2008, No. 199, which does not consider the possibility of using such combined therapeutic modalities as PAT. Conclusions. It is justified that in view of the tremendous exacerbation of the issue of Ukrainians’ mental health due to the war unleashed by Russia, it is recommended emergently amending the Resolution of the Cabinet of Ministers of Ukraine dated May 6, 2000, No. 770 (to transfer MDMA, DMT, psilocybin and psilocin from List 2 of Table 1 to List 2 of Table 2 of the relevant resolution) and taking measures to ensure the availability of PAT for people in need, in particular, by implementing an expanded access program.